Melatih Kecepatan Berpikir Serta Minat dan Bakat Murid SDN 060883 Medan Petisah - Hutapea, Endang; Harahap, Rahma Hayati; Ritonga, Fajar Utama (Medan Resource Center, 2023)
The Merdeka Belajar Kampus Merdeka (MBKM) program is an initiative developed by the partner institution of the University of North Sumatra (USU) to enhance the effectiveness of the elementary school (SD) learning process. In the context of the COVID-19 pandemic, where many schools are facing challenges in conducting effective teaching and learning processes, MBKM serves as an important solution. This program is focused on individual attention to students in developing their thinking skills, helping them explore their potential and personal interests, and overcoming the challenge of quick thinking. Currently, many elementary school students may struggle to develop quick thinking abilities and identify their interests and talents. This is due to their limited ability to work efficiently within a restricted timeframe. MBKM aims to bridge this gap, with the hope that the program will assist students in honing their mental efficiency, which, in turn, will provide significant benefits in meeting future demands. The MBKM program is expected to provide a solid foundation for student development, not only in learning but also in the discovery of personal interests and talents. In an ever-changing world, the ability to think quickly and efficiently will be a valuable asset, helping students become better prepared to face various challenges they may encounter in the future.